Structure, properties and applications of rhamnolipids produced by Pseudomonas aeruginosa L2-1 from cassava wastewater - Costa, Siddhartha G. V. A. O. [UNESP]; Nitschke, Marcia; Lepine, Francois; Deziel, Eric; Contiero, Jonas [UNESP] (Elsevier B.V., 2010)
The properties and applications of rhamnolipid surfactants produced by Pseudomonas aeruginosa L2-1 from cassava wastewater added with waste cooking oil (CWO) as low-cost substrate, were investigated and compared with the commercial rhamnolipid mixture JBR599 (Jeneil Biosurfactant Co., Saukville, USA). The rhamnolipids produced by strain L2-1 were characterized by high performance liquid chromatography-mass spectrometry. Sixteen different rhamnolipid congeners were detected, with Rha-C(10)-C(10) and Rha-Rha-C(10)-C(10) being the most abundant. The L2-1 rhamnolipids from CWO showed similar or better tensioactive properties than those from JBR599, with a minimal surface tension of 30 mN/m and a critical micelle concentration (CMC) of 30 mg/l. The L2-1 biosurfactants formed stable emulsions with several hydrocarbons and showed excellent emulsification of soybean oil (100%). These rhamnolipids removed 69% of crude oil present in contaminated sand samples at the CMC and presented antimicrobial activity against Bacillus cereus (32 mu g/ml), Micrococcus luteus (32 mu g/ml) and Staphylococcus aureus (128 mu g/ml). These results demonstrate that the rhamnolipids produced in ONO can be useful for industrial applications, such as the bioremediation of oil spills. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Rhamnolipids; P. aeruginosa; Cassava wastewater; Tensioactive properties; Oil removal